Bem Viver: neoliberalismo e unidade política - Osório, Vitor do Amaral (2016)
This thesis, Living Well: neoliberalism and political unity, seeks to analyse the proveniences of Living Well; and how a political unity within a territory is constructed connecting different peoples and cultures. The Ecuadorian indigenous movement has had a significant participation in this process while articulating the struggle for land and the recognition of the indigenous nationalities until they reached the position of the most relevant force within social society. The notion ofLiving Well is an effect of those struggles and an attempt to respond to the demands from the organized indigenous movement, while it follows the international directives on sustainable development. Knowledge and practices once subjected, such as the Sumak Kawasay, has become relevant to the process of continuous production and continuous participation characteristic of the effectiveness of the neoliberal rationality. In the case of Ecuador, the concept of Living Well has been introduced in the 2008 Ecuadorian Constitution, and it is part of the national planning based on human and nature rights. From a genealogical analysis perspective, it is our goal to expose how the struggles has composed the constructions of truth around the Living Well and which are the multiple elements connected by this notion